Special exercises to master topspin strokes in table tennis at sport specialization stage - Melnikov, Y. A.; Poryvkina, E. A. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to develop and practically substantiate a special set of exercises to help the trainee master topspin strokes at the sport specialization stage. Conclusion. The tennis players` technical mastery tests prior to the special topspin mastering exercises supplementary to the standard education and training process rated their skills on average as "satisfactory". The final tests demonstrated the proposed topspin training methodology being highly efficient as a supplementary component to the standard training system as it gives the means to improve the education and training process efficiency at the sport specialization stage and attain the expected result in a cost-efficient manner.